THE ROLE OF OMNICHANNEL STRATEGY AND SERVICE EXCELLENCE IN BEAUTY RETAIL - Isnaini, Fadila; Maulida, Astrid Sekarkinasih; Agustin, Harisatul (STIE PGRI Dewantara Jombang, 2024)
In the digital era, the beauty industry has experienced rapid growth driven by technological advancements and shifting consumer behavior. The omnichannel strategy has emerged as a key approach in beauty retail to create an integrated shopping experience and enhance customer loyalty. This study aims to analyze the impact of omnichannel strategy, relationship marketing, and service quality on customer satisfaction and loyalty in Indonesia’s omnichannel beauty retail. A quantitative approach with explanatory research design was employed. Data was collected from 191 respondents who are customers of omnichannel beauty retailers using a questionnaire analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that the omnichannel strategy, relationship marketing, and service quality significantly influence customer satisfaction. Meanwhile, customer loyalty is primarily driven by customer satisfaction, with omnichannel strategy and relationship marketing as supporting factors. These findings provide practical implications for business practitioners in designing more effective marketing strategies.